2012
DOI: 10.9790/3013-26105053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-phenyl-5-sulpha/substituted-3- substituted phenyl azo indoles used as antifertility agent

Abstract: Abstract--A novel series of 2-phenyl-5-sulpha/substituted-3-phenyl substituted azo indoles have been synthesized and tested as an antifertility activity in mature albino mice. The tested compounds showed significant antifertility activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Study of Candea et al, (2009) [23] revealed the antiturbercular activity of 7-chloro-4-quinolinylhydrazones derivatives; 7-Choloro-4-methoxy-3methylquinoline. 1H-Indole,5-methyl-2-phenyl is a nitrogen containing heterocyclic molecule widely nd in plants, which has antibacterial and anti-in ammatory activity [24]. Hexadecanoic acid, methyl ester and Octadecanoic acid are Decanoic acid derivatives and have antimicrobial, anti-in amatory, hypercholesteromic, anticancer and lubricant properties.…”
Section: Screenings Of Phytochemicals Using Gc-msmentioning
confidence: 99%
“…Study of Candea et al, (2009) [23] revealed the antiturbercular activity of 7-chloro-4-quinolinylhydrazones derivatives; 7-Choloro-4-methoxy-3methylquinoline. 1H-Indole,5-methyl-2-phenyl is a nitrogen containing heterocyclic molecule widely nd in plants, which has antibacterial and anti-in ammatory activity [24]. Hexadecanoic acid, methyl ester and Octadecanoic acid are Decanoic acid derivatives and have antimicrobial, anti-in amatory, hypercholesteromic, anticancer and lubricant properties.…”
Section: Screenings Of Phytochemicals Using Gc-msmentioning
confidence: 99%